Hukum Nikah Beda Agama - Ipandang Ipandang (Al-'Adl, 2009)
In attitude, the happening of condition at structural life of this adult Indonesia society, especially in life keep house, there are one of the problems which do not newly, but again practiced many by some groups of prenatal life of society social like all celebrities, artist of Indonesia, and also some Indonesia society groups in general, which is there are as Moslem but marriage with a different couple of religion. So !, how Islam view to this problem?